UMP Press, Perbadanan Kota Buku intensify book marketing efforts to international market - Athirah, Ruzaini; Nur Hartini, Mohd Hatta (UMPSA, 2022)
PEKAN, 3 December 2021 - Universiti Malaysia Pahang (UMP) Press and Perbadanan Kota Buku (PKB) have entered a strategic collaboration involving various segments of collaboration, especially in the promotion and marketing of books to the international market, to share the same values and aspirations for the future and sustainability of the country’s book industry.